Combined Oral Contraceptive Treatment Does Not Alter the Gut Microbiome but Affects Amino Acid Metabolism in Sera of Obese Girls With Polycystic Ovary Syndrome - Tayachew, Beza; Vanden Brink, Heidi; Garcia-Reyes, Yesenia; Rahat, Haseeb; D'Alessandro, Angelo; Frank, Daniel N.; Robertson, Charles E.; Silveira, Lori; Kelsey, Megan; Pyle, Laura; Cree-Green, Melanie (Frontiers in Physiology, 2022)
The gut microbiome is altered in obese adolescents with polycystic ovary syndrome (PCOS), and is associated with free testosterone, metabolic markers, and insulin resistance. Combined oral contraceptives (OCP) are a primary treatment for PCOS and decrease testosterone, but the effect on the serum metabolome or gut microbiome in obese adolescents with PCOS is unknown. Contrast gut microbiome profiles, targeted serum metabolomics, hormone levels, and metabolic measures in adolescents with PCOS and obesity with and without OCP treatment. Adolescent girls with obesity and PCOS underwent stool and fasting blood collection and MRI for hepatic fat fraction. Fecal bacteria were profiled by high-throughput 16S rRNA gene sequencing and fasting serum metabolomics performed with high resolution mass spectrometry. Groups were contrasted using t-tests and principle least squares discrimination analysis (PLS-DA). Associations between bacterial taxa, baseline metabolic measures, hormone levels and the metabolome were conducted using Spearman analysis. Analyses were adjusted for false discovery rate. Twenty-nine adolescents with obesity [Untreated N=21, 16±1.2 years, BMI%ile 36.5± 3.0; OCP N=8, 15.5±0.9 years, BMI%ile 32.5±3.9] participated. Of the untreated adolescents, N=14 contributed serum for metabolomic analysis. Participants on OCP therapy had lower free testosterone and free androgen index (p<0.001) and higher sex hormone binding globulin. There was no difference in measures of fasting glucose, insulin, lipids or HOMA-IR between groups. PLS-DA of serum metabolomics showed discrimination between the groups, secondary amino acid changes. Untreated and OCP had similar stool microbiome α-diversity based on evenness (p=0.28), richness (p=0.39), and Shannon diversity (p=0.24) and global microbial composition (-diversity, p=0.56). There were no differences in % relative abundance at any level. Bacterial α-diversity was negatively associated with serum long chain fatty acids and branched chain amino acids. A higher %relative abundance of family Ruminococcaceae was significantly associated with serum bile acids and HOMA-IR. Despite hormone and serum amino acid differences, girls treated with OCP had similar metabolic and gut microbiome profiles compared to the untreated PCOS group. The association between bacterial α-diversity, Ruminococcaceae, clinical markers and long chain fatty acids suggests a potential role of the gut microbiome in the pathogenesis of the metabolic comorbidities in PCOS.